2015
DOI: 10.1136/annrheumdis-2015-207751
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against carbamylated proteins are present in primary Sjögren's syndrome and are associated with disease severity

Abstract: ObjectivesHerein, we investigate the presence and prognostic value of autoantibodies against carbamylated proteins (anti-CarP) in the serum of patients with primary Sjögren's syndrome (pSS).Patients and methodsSerum levels of anti-CarP antibodies were measured in Norwegian patients with pSS (n=78) and corresponding controls (n=74) using ELISA and analysed in relation with exocrine gland function, degree of salivary gland inflammation, signs of ectopic germinal centre (GC) formation and immunological markers. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
2
23
1
1
Order By: Relevance
“…Anti-CarP was also present in 50% of patients with spondyloarthritis, although only 8 patients were studied in this group. These results build on other recent studies including one by Bergum and colleagues that similarly found an increased prevalence of anti-CarP antibodies in patients with primary Sjögren syndrome 8 .…”
Section: Rheumatologysupporting
confidence: 89%
“…Anti-CarP was also present in 50% of patients with spondyloarthritis, although only 8 patients were studied in this group. These results build on other recent studies including one by Bergum and colleagues that similarly found an increased prevalence of anti-CarP antibodies in patients with primary Sjögren syndrome 8 .…”
Section: Rheumatologysupporting
confidence: 89%
“…Beside patients with RA, anti-CarP antibodies were present in a small number of patients with SLE and SS; less than one third of these patients also displayed ACPA positivity. These results can be partially attributed to erosive joint disease described in a small percentage of patients with SLE [21]; besides, carbamylation can be enhanced in patients with kidney involvement or in those with active inflammatory status [8]. Similarly, a clear link between antibody production and the degree of inflammation has been shown in patients with SS, as the activity of circulating myeloperoxidase (MPO), which catalyzes the production of cyanate from thiocyanate, seems to be significantly increased [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a clear link between antibody production and the degree of inflammation has been shown in patients with SS, as the activity of circulating myeloperoxidase (MPO), which catalyzes the production of cyanate from thiocyanate, seems to be significantly increased [20]. Two studies investigated anti-CarP in patients with SLE and with SS [20, 21]. The detection of a subset of anti-CarP-positive subjects among patients with SLE or SS and joint involvement suggests the possibility of that anti-CarP might serve as a serological marker for erosive arthritis in AIRDs other than RA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to anti-BPI responses, the lack of association between ACarPa and anti-Cif IgG levels suggests that ACarPA arise independently of infection and are most likely a marker of neutrophil-driven bronchial inflammation reported in other chronic diseases (24,68,69). Alternatively, it may be that ACarPA influence clinical phenotype by impairing the antibacterial activity on NETs.…”
Section: Discussionmentioning
confidence: 51%